Numerical Calculation Method for Crack Dynamic Propagation Based on Newmark Implicit Time Integration Scheme - GUO Deping, LI Zheng, PENG Senlin, ZENG Zhikai, WU Daifeng (Shanghai Jiaotong Daxue xuebao, 2021)
Extended finite element method (XFEM) is based on the idea of unit decomposition. The jump function that can reflect the discontinuity of the crack surface and the progressive displacement field function of the crack tip is added to the conventional finite element displacement mode, which avoids the inconvenience of remeshing the crack tip and the heavy calculation. Then the conventional finite element method calculates the fracture problem, and the crack propagation is independent of the mesh. When the standard finite element deals with time integration, the degree of freedom of the overall stiffness matrix will continue to increase in the process of crack propagation, which makes iterative calculation impossible. This paper proposes a novel Newmark implicit time integration scheme based on the XFEM to simulate dynamic crack growth. This method enriches all the nodes with the Heaviside function and the asymptotic displacement field function at the crack tip, that is, each node has 12 degrees of freedom, so that the overall stiffness matrix is consistent without making iterative calculation impossible. At the same time, a sparse matrix technology is proposed to solve the problems of large memory and long calculation time occupied by the matrix.